Rate and Clinical Presentation of Macrophage Activation Syndrome in Patients With Systemic Juvenile Idiopathic Arthritis Treated With Canakinumab. Issue 1 (January 2016) - Grom, Alexei A.; Ilowite, Norman T.; Pascual, Virginia; Brunner, Hermine I.; Martini, Alberto; Lovell, Daniel; Ruperto, Nicolino; ,; Leon, Karolynn; Lheritier, Karine; Abrams, Ken
Abstract : Objective: In pivotal trials, canakinumab has been shown to be effective in the treatment of systemic juvenile idiopathic arthritis (JIA), but reported adverse events have included macrophage activation syndrome (MAS). This study was undertaken to assess the impact of canakinumab on MAS incidence. Methods: An independent MAS Adjudication Committee (MASAC), consisting of 3 of the authors, was convened, and a search of databases from clinical studies of canakinumab treatment in systemic JIA was performed using MASAC‐specified adverse event terms to identify potential MAS events. These were then adjudicated as "probable MAS, " "possible MAS, " or "MAS unlikely, " using criteria developed by the MASAC. MAS rates were expressed as numbers of cases per 100 patient‐years. Results: Of 72 potential MAS cases identified, 21 events (19 with canakinumab treatment; 2 with placebo treatment) in 19 patients were adjudicated as being probable MAS and 10 events in 9 patients as being possible MAS. Systemic JIA was well controlled in the majority of canakinumab‐treated patients at the time of MAS. The time period between initiation of canakinumab treatment and onset of MAS ranged from 3 to 1, 358 days (median 292 days). When the rates of probable MAS events were compared between canakinumab‐treated patients (2.8 per 100 patient‐years) and placebo‐treated patients (7.7 per 100 patient‐years), the difference was not significant (−4.9 [95% confidence interval −15.6, 5.9]). There were 3 deaths due to MAS‐related complications (2 in patients receiving canakinumab; 1 in a patient receiving placebo); full recovery was reported in all other patients. Infections were the most common trigger of MAS, and the clinical features of MAS were not modified by canakinumab. Conclusion: Canakinumab does not have a significant effect on MAS risk or its clinical features in patients with systemic JIA. Infections are the most common trigger, and MAS occurs even in patients whose systemic JIA is well controlled with this treatment.